Utilização do meloxicam para reduzir respostas Inflamatórias em bovinos de corte transportados - Guarnieri Filho, Thomaz Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This experiment evaluated the effects of meloxicam administration on physiological and performance responses of transported cattle during feedlot receiving. Eighty-four Angus × Hereford steers were ranked by BW on d -10, and assigned to 21 dry lot pens. From d -10 to 0, pens were fed Alfalfa-grass hay ad libitum and 2.4 kg/steer daily (DM basis) of a corn-based concentrate. On d 0, pens were randomly assigned to: 1) transport for 1,440 km in a livestock trailer and oral administration of meloxicam (1 mg/kg of BW) at loading (d 0), unloading (d 1), and daily from d 2 to 7 of feedlot receiving (MEL; n = 7), 2) same transportation and treatment schedule of MEL, but oral administration of lactose monohydrate (1 mg/kg of BW) instead of meloxicam (TRANS; n = 7), or 3) no transport and oral administration of lactose monohydrate (1 mg/kg of BW) concurrently with treatment administration to MEL and TRANS (CON; n = 7). Upon arrival (d 1), MEL and TRANS steers returned to their pens for a 21-d feedlot receiving with the same diet offered from d -10 to 0. Treatments were administered to steers via oral drench on d 0 and 1, or mixed daily with the concentrate from d 2 to 7. Full BW was recorded prior to (d -2, -1, and 0) treatment application and at the end of experiment (d 20, 21, and 22) for ADG calculation. Daily DMI was recorded from d 1 to 21. Blood samples were collected on d 0, 1, 3, 5, 7, 10, 14, and 21. During the initial 7 d of feedlot receiving, hay and total DMI were reduced (P ≤ 0.03) in TRANS vs. CON and MEL, similar between CON and MEL (P ≥ 0.26), whereas concentrate DMI did not differ (P = 0.16) among ...

Este experimento analisou os efeitos da administração do meloxicam nas respostas fisiológicas e no desempenho de bovinos na fase inicial do confinamento após serem transportados. Foram utilizados 84 bezerros Angus × Hereford, divididos por peso vivo (PV) no dia -10 do experimento e distribuídos em 21 baias de confinamento. Do d -10 ao d 0, todos os animais receberam uma dieta composta por feno de alfalfa a vontade e 2,4 kg/animal (base MS) de um concentrado a base de milho. No dia 0, todas as baias foram aleatoriamente atribuídas a receberem um dos seguintes tratamentos: 1) transporte por 1.440 km em um caminhão comercial e administração oral de meloxicam (1 mg/kg do PV) no carregamento (d 0), no descarregamento (d 1) e diariamente do d 2 ao d 7 no período inicial de confinamento (MEL; n = 7), 2) transporte e administração do tratamento nos mesmos dias do grupo MEL, porém com lactose monohidratada (1 mg/kg do PV) (TRANS; n = 7), 3) ausência de transporte e administração de lactose monohidratada (1 mg/kg do PV) nos mesmos dias dos tratamentos MEL e TRANS (CON; n = 7). Logo após o descarregamento (d 1), todos os animais dos tratamentos MEL e TRANS retornaram para suas respectivas baias para o período de 21 dias de confinamento, recebendo a mesma dieta oferecida do d -10 ao d 0. Nos dias 0 e 1, os tratamentos foram aplicados através de solução aquosa e administrados via oral, porém dos dias 2 ao 7, os tratamentos foram misturados no concentrado. Para o cálculo de ganho peso diário (GPD) foram utilizados as médias de ...
Keywords: Bovino de corte; Bovino - Infecções; Proteinas - Sintese; Confinamento (Animais); Meloxicam; Animais - Transporte; Feedlots